Activating happiness : a jump-start guide to overcoming low motivation, depression, or just feeling stuck - Hershenberg, Rachel (New Harbinger Publications, Inc., 2017)
--Activating Happinessreally feeling better, instead of just reassuring others. You'll learn to set healthy goals for your body like eating and sleeping well, as well as healthy goals for your mind. Most importantly, you'll discover how to view your life through the lens of your own deepest values, which will spark a commitment to real, lasting change. The best thing about change is that you can start anywhere. By building a life--moment by moment--of rewarding behaviors that correspond to your values, you have the recipe for getting and staying well at your fingertips. This book will guide your way.